"Being all alone makes me sad": loneliness in older adults with depressive symptoms. (September 2014) - van Beljouw, Ilse M. J.; van Exel, Eric; de Jong Gierveld, Jenny; Comijs, Hannie C.; Heerings, Marjolijn; Stek, Max L.; van Marwijk, Harm W. J.
ABSTRACT Background: The consequences of co-occurring persistent loneliness and late life depression are yet unknown. The aim of this study was to get a deeper insight into the mental health consequences of loneliness in older persons with depressive symptoms and their perspectives of emotional distress by using a mixed-methods study design. Methods: Two hundred and forty nine community-dwelling older persons with depressive symptoms according to the Patient Health Questionnaire-9 (≥6) were included. A validated cut-off score on the Loneliness Scale was used to distinguish lonely elders from elders who were not lonely. Quantitative and qualitative data were used to examine differences in mental health and perspectives on emotional distress between lonely and not lonely older persons with depressive symptoms. Results: Loneliness was highly prevalent among older persons with depressive symptoms (87.8%). Lonely people suffered from worse mental ill-health (e.g., more severe depressive symptoms, more often a depressive disorder and a lower quality of life) compared to not lonely individuals. Depressive symptoms were regarded as a logical consequence of loneliness. Lonely people perceived little command over their situation: causes of loneliness were attributed externally to perceived deficits in their social networks and they mainly expressed the need to be listened to. Conclusion: Our findings underline the importance of paying considerable attention to (severe) loneliness in older adults with depressive symptoms given its high prevalence and serious mental health consequences. Future studies should look into whether addressing loneliness when discussing depressive symptoms in clinical practice may provide an opportunity to better adjust to older persons' depression perceptions and might therefore improve care utilization.